The surf's up collection [large type] : (A tide worth turning, message in a bottle, the shell collector's daughter) - Wiseman, Beth, 1962- (Thorndike Press large print Christian romance series., 2025)
Each Surf's up novella takes the reader to a beach locale, weaving romance and adventure into a soul-soothing journey of hope.